Peran Manajemen Gembala Sidang Sebagai Strategi Misi Dalam Mewujudkan Pertumbuhan Gereja - Parhusip, Mangatas; Saragih, Jelly Pridayani; Petrus Riko Manik; Puput Novel Manalu; Restia Sitorus (Universitas Methodist Indonesia, 2025)
This study seeks to examine the pivotal role of pastoral management competencies and mission strategies in enhancing the quality of ministry as a means of fostering church growth. The research employs a qualitative method, utilizing library research to obtain the required data and information. The findings indicate that the application of fundamental management principles within the church, namely planning, organizing, directing, coordinating, and controlling, positively contributes to the improvement of pastoral ministry quality, positioning the pastor as a spiritual leader whose role is crucial to the effectiveness of church services. Furthermore, effective pastoral management encourages active participation among congregational members in fulfilling the church’s calling of fellowship, witness, and service, thereby advancing church growth in terms of quality, quantity, and organic.